Ragam Bahasa Indonesia Pada Bidang Pariwisata: Studi Kasus Penggunaan Bahasa Indonesia di dalam Bus Pariwisata - Almalya Dewita Syawwal; Salma Fatin Nabilah (Jurnal Riset Rumpun Ilmu Bahasa, 2023)
The purpose of this article is to find out the use of Indonesian language that has been reduced in use which has been changed into foreign languages, especially in tourism bus transportation. Tourism in Indonesia is an important economic sector. In 2009, tourism ranked third in terms of foreign exchange earnings after oil and gas and palm oil commodities. Currently, the tourism business is growing rapidly in Indonesia because the tourism sector is driven as a very large labor recruiter and a very large source of economic income in Indonesia, a factor that supports the existence of tourism is Indonesia's strategic territory and a large selection of destinations. The use of Indonesian today has changed a lot where Indonesian is replaced by foreign languages, especially in the tourism sector, such as the use of the word "souvenir" which is currently changing its nickname to "souvenir" the problem in this article is the threat that greatly affects the use of Indonesian. This method uses the observation method in the form of interviews. As a result of this analysis, there is a change in Indonesian language style to foreign languages, especially English.